Survey research in social science with complete samples - Mohd Ghani, Awang; Diyana, Kamarudin (Penerbit UMP, 2017)

(untitled)
Civilization in human life begins by the research outcomes starting from trial and errors activities till working in the laboratory. Research is a tool in improving life on earth as what Maslow said in his theory, human being life objective is to achieve the level of self-actualization or Nirvana in Hinduism belief or “ah sani taqwim” in Islamic point of view as well as “Nirwana” in the Malay custom. Research is a tool of finding more knowledge, adding the existing knowledge or finding new solution towards the problem aroused or completing a body of knowledge.